Robust H Infinity Control for Discrete-Time Switched Linear Systems Subject to Exponential Uncertainty - Changlin Li; Fei Long; Changzhen Cui (ICICTA : 2008 International Conference on Intelligent Computation Technology and Automation : 20-22 October 2008, 2008)
In this paper, we address the robust H infin control problem of discrete-time switched linear systems with exponential uncertainties. By using Taylor series approximation and convex polytope technique, exponential uncertain discrete-time switched linear system is transformed into an equivalent switched polytopic model with an additive norm bounded uncertainty. For such equivalent switched model, we design its switching strategy and associated state feedback sub-controllers so that such switched model is asymptotical stabilization with H infin disturbance attenuation based on multiple Lyapunov function technology and LMI approach.